2016
DOI: 10.1186/s40623-016-0433-1
|View full text |Cite
|
Sign up to set email alerts
|

Spread F occurrence and drift under the crest of the equatorial ionization anomaly from continuous Doppler sounding and FORMOSAT-3/COSMIC scintillation data

Abstract: A relatively new method based on measurements by multipoint continuous Doppler sounding is applied to study the occurrence rate, propagation velocities, and directions of spread F structures over Tucumán, Northern Argentina, and Taiwan, both of which were under the crest of the equatorial ionization anomaly in 2014. In addition, spread F is studied globally over the same time period from the S4 scintillation index measured onboard FORMOSAT-3/COSMIC (F3/C) satellite. It is shown that the continuous Doppler soun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Alfonsi et al (2013) reported a maximum spread-F occurrence in local summer in Tucumán from October 2010 to September 2011. Using continuous Doppler sounding, Chum et al (2016) reported that most of the spread F events over Tucumán were observed during local summer. Chen et al (2006) described the equatorial F region irregularities in two Peruvian stations from April 1999 to March 2000.…”
Section: Plasma Bubbles Occurrence Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Alfonsi et al (2013) reported a maximum spread-F occurrence in local summer in Tucumán from October 2010 to September 2011. Using continuous Doppler sounding, Chum et al (2016) reported that most of the spread F events over Tucumán were observed during local summer. Chen et al (2006) described the equatorial F region irregularities in two Peruvian stations from April 1999 to March 2000.…”
Section: Plasma Bubbles Occurrence Ratementioning
confidence: 99%
“…In the Brazilian region, earlier works showed a high plasma bubble occurrence rate during the December solstice and a low occurrence during the June solstice (Abdu et al 1998;Sahai et al 1994). Chum et al (2016) examined the spread-F behaviour over Tucumán and Taiwan in 2014 based on measurements by continuous Doppler sounding. They observed the highest occurrence rate from September to March in Tucumán, and around equinoxes in Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…By using a constellation of satellites equipped with the GNSS receivers, radio occultation (RO) scintillation is utilized to detect the location and height of the plasma irregularities (e.g. Chang et al., 2018; Chum et al., 2016; Huang et al., 2014; Liu et al., 2016; Wu et al., 2005). Those RO scintillation intensities are measured in a very similar magnitude of strength in comparison with the ground‐based scintillation observations (Chen et al., 2017), and show a similar distribution of EPBs to those using satellite in situ plasma measurements (e.g.…”
Section: Radio Occultation and F7/c2mentioning
confidence: 99%
“…Both the ground based measurements and satellite radio occultation measurements of S4 were used. Chum et al (2016b) studied occurrence rates of spread F, longitudinal distribution of spread F occurrence rates and zonal drift velocities of spread F and concluded that all the instruments provided consistent results.…”
Section: Introductionmentioning
confidence: 97%
“…spread F. Spread F, especially at low latitudes, can significantly deteriorate the quality of GPS (GNSS) signal and decrease the precision of position determination. Chum et al (2016b) compared the observation of equatorial (low-latitude) spread F by ionosondes, CDSs, and GPS (GNSS) receivers. The spread F was detected by GPS receivers as high values of the scintillation index S4.…”
Section: Introductionmentioning
confidence: 99%